Pathogenic tau decreases nuclear tension in cultured neurons - Sohn, Claira; Ma, Jiacheng; Ray, William J.; Frost, Bess (Frontiers in Aging, 2023)
Neurodegenerative tauopathies, including Alzheimer’s disease, are pathologically defined by the presence of aggregated forms of tau protein in brains of affected individuals. Previous studies report that the negative effects of pathogenic tau on the actin cytoskeleton and microtubules cause a toxic destabilization of the lamin nucleoskeleton and formation of nuclear invaginations and blebs. Based on the known function of the nucleus as a mechanosensor, as well as the high incidence of nuclear pleomorphism in human Alzheimer’s disease and related tauopathies, we investigated the effects of pathogenic tau on nuclear tension. We first find that tau-dependent nuclear envelope invagination and relocalization of LInker of Nucleoskeleton and Cytoskeleton (LINC) complex components are conserved in a newly-developed neuroblastoma cell line that features doxycycline-inducible expression of a tau mutant associated with autosomal dominant frontotemporal dementia. We next determine that a Förster resonance energy transfer (FRET)-based sensor of nuclear tension responds to cytoskeletal stabilization and destabilization when expressed in neuroblastoma cells. Using this nuclear tension sensor, we find that induced expression of pathogenic tau is sufficient to decrease nuclear tension. This work provides the initial proof-of-concept evidence that pathogenic forms of tau alter nuclear tension, paving the way for the future study of altered nuclear mechanosensing in the context of tau-mediated neurodegenerative disorders.